Induction of Oodev Hormone to increase Gonad Maturity Rate Female Betta Fish (Betta splendens) Through Feed - Lestari, Tuti Puji; Farida, Farida; Merli, Merli (Universitas Malikussaleh, 2022)
Betta fish are freshwater ornamental fish that are very popular and have quite high economic value, but the reproductive process still depends on the spawning season, so an increase in reproductive potential is needed. The experiment was conducted in order to determine the role of each induction Oocite development (Oodev) hormone in the diet to betta fish female final maturation process and morphology gonads. Completely randomized design (CRD) with one factor consisting of 5 treatments and 3 replications.The main factors are Oodev hormone dosage: 0.0 mL.kg-1 fish weigh; 0.5 mL.kg-1 fish; 1.0 mL.kg-1 fish; 1.5 mL.kg-1 fish and 2.0 mL.kg-1 fish. We used 135 female broodstock with an initial weight range ± 1-2.15 g.ekor-1 and at stage II of gonad maturation. Fish were fed three a day at 07.00 am, 12.00 am, and 05.00 pm at satiation level during 45 days. During the final maturation, gonad morphology, survival rates, and water quality were observed. The results show that Oodev hormone induction could improve final maturation up to 266.66%. This result is comparatively higher than 0.0 mL.kg-1 and 0.5 mL.kg-1 fish hormone induction and produces 100% of mature broodstock. Thus, the Oodev hormone induction at optimal dose of 1.16 mL.kg-1 of fish can improve the induction maturation up to 2-3 times faster maturation frequency on the out of spawning seasonKeywords:Female Betta splendens; final maturation; Oodev; feed